Early Maladaptive schemas and Premenstrual syndrome in mothers with postpartum depression - Alimoradi B; Nejat H (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Mood disorders constitute a prevalent problem during postnatal period. Nonetheless, three is not adequate information on the underlying mechanism of postpartum depression (PPD). Objectives: Therefore, this study aimed to investigates the role of early maladaptive schemas (EMSs) and premenstrual syndrome (PMS) in mothers with postpartum depression (PPD) referring to health centers in Mashhad. Methods: In order to carry out this cross-sectional study purposeful sampling was used to select 179 mothers who referred to health centers in Mashhad during February, March, and April of 2018 and met the relevant criteria of study as the participants. Participants completed Young's Early Maladaptive Schema, Premenstrual syndrome (PSST) and the Edinburgh Depression Scale. Descriptive statistics and stepwise regression analysis were used to analyze the data with SPSS version 20. Results: The participants ranged in age from 19 to 41 and their mean age was 29.7±8/7. This group of participants consisted of 106 mothers who had experienced their first delivery, 42(24.4%) mothers who had experienced their second delivery, and 24(14%) mothers who had experienced their third delivery. The results revealed that PMS (P<0/001; r=0.56) and EMSs (P<0/05; r=0.65) had significant correlations with PPD. PMS and EMSs together predicted 42% of the variance of PPD. Conclusion: The findings of this study suggests that PMS and EMSs affect mothers' PPD